2016
DOI: 10.3892/etm.2016.3644
|View full text |Cite
|
Sign up to set email alerts
|

Blood-filled cerebrospinal fluid-enhanced pericyte microvasculature contraction in rat retina: A novel in vitro study of subarachnoid hemorrhage

Abstract: Previously, it was widely accepted that the delayed ischemic injury and poor clinical outcome following subarachnoid hemorrhage (SAH) was caused by cerebral vasospasm. This classical theory was challenged by a clazosentan clinical trial, which failed to improve patient outcome, despite reversing angiographic vasospasm. One possible explanation for the results of this trial is the changes in microcirculation following SAH, particularly in pericytes, which are the primary cell type controlling microcirculation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…In any case, the observed microvascular changes resemble aSAH-induced changes in large caliber vessels, namely early cerebral artery vasoconstriction and an associated reduction in cerebral perfusion which may contribute to DCI in some patients ( 33 35 ). Considering that increased intracranial pressure during the acute phase of aSAH forces subarachnoid blood into the preretinal space, a significant reduction in retinal vessel diameters observed during the early phase after aSAH is in line with previous in vitro and in vivo animal studies showing that blood-filled cerebrospinal fluid enhances constriction of both, the retinal ( 36 ) and cerebral ( 37 ) microvasculature. Interestingly and in contrast to angiographic vasospasm, which usually dissolves by week 2 after the ictus ( 34 ), however, there was almost no return of arterial and venous diameters toward the control level during the first 3 weeks after aSAH and only a partial, non-significant recovery at follow-up more than 6 weeks later.…”
Section: Discussionsupporting
confidence: 89%
“…In any case, the observed microvascular changes resemble aSAH-induced changes in large caliber vessels, namely early cerebral artery vasoconstriction and an associated reduction in cerebral perfusion which may contribute to DCI in some patients ( 33 35 ). Considering that increased intracranial pressure during the acute phase of aSAH forces subarachnoid blood into the preretinal space, a significant reduction in retinal vessel diameters observed during the early phase after aSAH is in line with previous in vitro and in vivo animal studies showing that blood-filled cerebrospinal fluid enhances constriction of both, the retinal ( 36 ) and cerebral ( 37 ) microvasculature. Interestingly and in contrast to angiographic vasospasm, which usually dissolves by week 2 after the ictus ( 34 ), however, there was almost no return of arterial and venous diameters toward the control level during the first 3 weeks after aSAH and only a partial, non-significant recovery at follow-up more than 6 weeks later.…”
Section: Discussionsupporting
confidence: 89%
“…Normal cerebrospinal fluid were purchased from United States BIOLOGical (Catalog: 3052). BCSF was prepared following Foley’s and u’sds 15,16 . Briefly, donor patient arterial blood and normal cerebrospinal fluid under aseptic condition were mixed with 1:1 ratio and incubated in a 37 °C water bath for 24 h. Then, the mixed samples were centrifuged at 10,000 × g for 20 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study indicated that pericytes bidirectionally control microvessel diameters and regulate cerebral blood flow [4]. Our previous study further demonstrated that pericyte α-SMA phenotype transformation caused acute microvessel/pearl-like constriction and neurological deficits in the setting of SAH [5,6]. However, a recent study suggested that pericytes might have a negative influence on neurovascular integrity and cause neuronal degeneration in apolipoprotein E-deficient mice [7].…”
Section: Introductionmentioning
confidence: 80%